Inclusive education and labour market insertion from a capabilities approach: a phenomenological and functional diversity perspective - Zárate Rueda, Ruth; Murallas-Sánchez, Daniella; Ortega-Zambrano, Catalina (Revista de Investigación Educativa, 2021)
This study focuses on the analysis of life experiences in the academic and work environment of professionals with functional diversity graduated from the Universidad Industrial de Santander-UIS. Our research has been conducted under the interpretative paradigm and uses a phenomenological approach in order to evaluate the participants’ lived and felt experiences during and after their time at university. Our results have been validated through the use of triangulation, contrasting the information gathered from theory, reality and researchers. The results indicate that architectural and psychosocial barriers are an obstacle to the differential needs of students from the perspective of inclusive education; besides, it has been found that the labour market does not offer inclusive opportunities, and participation is limited. This has led us to conclude that there are gaps in access to education and work regarding equal opportunitiesand the respect for differences. Finally, we note that the implementation of Inclusive Education Policies at university is essential for the integration of this demographic, specifically in processes that combine the Capabilities and Human Rights approaches.